The Basis and Applications of the Action Fluency and Action Naming Tasks - Beber,Bárbara Costa (2014)
ABSTRACT The Action Fluency (AF) and Action Naming (AN) are different tasks involving verb generation. Evidence indicates that verb tasks yield different information from that obtained with nouns. Objective: This study aimed to analyze the information available in the scientific literature on the mechanism and clinical application of these tasks. Methods: We carried out a systematic review of the literature and the findings were presented according to clinical studies and neuroimaging studies, and to the task in question. Results: The literature contained a variety of relevant studies with different objectives, methodologies and populations. After the analysis (exclusion criteria) of the studies obtained by the search terms, only 40 studies were included in this review. Conclusion: It was possible to conclude that AF and AN involve different brain processes, and although recruiting frontal areas and circuits, other areas are also critical. These tasks may be useful for differentiating Primary Progressive Aphasias; AF might represent a new measure of executive function; finally, both these tests can be used to provide a better understanding of cognitive processes and certain diseases.